Spatiotemporal quantitative microRNA-155 imaging reports immune-mediated changes in a triple-negative breast cancer model - Skourti, Elena; Volpe, Alessia; Lang, Cameron; Johnson, Preeth; Panagaki, Fani; Fruhwirth, Gilbert O. (Frontiers in Immunology, 2023)
MicroRNAs are small non-coding RNAs and represent key players in physiology and disease. Aberrant microRNA expression is central to the development and progression of cancer, with various microRNAs proposed as potential cancer biomarkers and drug targets. There is a need to better understand dynamic microRNA expression changes as cancers progress and their tumor microenvironments evolve. Therefore, spatiotemporal and non-invasive in vivo microRNA quantification in tumor models would be highly beneficial. Here, we developed an in vivo microRNA detector platform in which the obtained signals are positively correlated to microRNA presence, and which permitted stable expression in cancer cells as needed for long-term experimentation in tumor biology. It exploits a radionuclide-fluorescence dual-reporter for quantitative in vivo imaging of a microRNA of choice by radionuclide tomography and fluorescence-based downstream ex vivo tissue analyses. We generated and characterized breast cancer cells stably expressing various microRNA detectors and validated them in vitro. We found the microRNA detector platform to report on microRNA presence in cells specifically and accurately, which was independently confirmed by real-time PCR and through microRNA modulation. Moreover, we established various breast tumor models in animals with different levels of residual immune systems and observed microRNA detector read-outs by imaging. Applying the detector platform to the progression of a triple-negative breast cancer model, we found that miR-155 upregulation in corresponding tumors was dependent on macrophage presence in tumors, revealing immune-mediated phenotypic changes with these tumors as they progressed. While applied to immunooncology in this work, this multimodal in vivo microRNA detector platform will be useful whenever non-invasive quantification of spatiotemporal microRNA changes in living animals is of interest.